INFLUENCE OF PHYSICAL AND SOCIAL FACTORS ONPLACEATTACHMENT IN DEMANDAILING CAFE - Astrid Kusumowidagdo; Aubrey Michelle (Ide dan Dialog Desain Indonesia (Idealog), 2023)
In this modern era, after the end of the pandemic, cafes are back as the third space of choice forthe majority of urban communities. Of ices and homes are no longer a priority as a place to do of ice tasks orschool and campus assignments. The purpose of this study is to see visitors' perceptions of the interior of DeMandailing cafe in West Surabaya whether physical and social factors af ect the increase in productivitywhile working in the cafe. The research method was carried out by means of a case study to 100 people withan age limit of 18-40 years, where they filled out a survey to determine place attachment based on physical factors and social factors. Physical factors include cleanliness aroma, natural lighting, artificial lighting, furniture comfort, music and acoustics, the decor used, and social factors include the desire to stay long, feeling a sense of belonging, the ability to feel territorial, having feelings of trust for staf , increasedproductivity, the desire and opportunity to socialize with others. The conclusion obtained in terms of physical factors, the design in the cafe succeeds in attracting visitors to enter and is comfortable to work and socializewith others. In terms of social factors, it is also quite supportive, but still needs to improve the design sothat it becomes a stimuli to encourage socialization activities. Keywords : Place attachment, cafe interior, physical factors, social factors.